2021
DOI: 10.1177/00222429211045687
|View full text |Cite
|
Sign up to set email alerts
|

Blame the Bot: Anthropomorphism and Anger in Customer–Chatbot Interactions

Abstract: Chatbots have become common in digital customer service contexts across many industries. While many companies choose to humanize their customer service chatbots (e.g., giving them names and avatars), little is known about how anthropomorphism influences customer responses to chatbots in service settings. Across five studies, including an analysis of a large real-world dataset from an international telecommunications company and four experiments, the authors find that when customers enter a chatbot-led service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
200
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 269 publications
(242 citation statements)
references
References 59 publications
6
200
1
Order By: Relevance
“…Moreover, as there is only limited information available on anthropomorphic chatbots for commercial purposes, we focus on digital agents as a sales and marketing channel rather than a customer service solution. This study further differs from earlier papers as we performed a practical experiment, whereas other authors have measured effects basically by displaying illustrations [ 17 ]. Sheehan et al [ 71 ] confirmed that the validity of results can be improved by asking participants to experimentally engage with and subsequently rate a conversational agent.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Moreover, as there is only limited information available on anthropomorphic chatbots for commercial purposes, we focus on digital agents as a sales and marketing channel rather than a customer service solution. This study further differs from earlier papers as we performed a practical experiment, whereas other authors have measured effects basically by displaying illustrations [ 17 ]. Sheehan et al [ 71 ] confirmed that the validity of results can be improved by asking participants to experimentally engage with and subsequently rate a conversational agent.…”
Section: Introductionmentioning
confidence: 66%
“…The few references published to date addressing the humanization of chatbots focus mainly on those implemented in customer service-related scenarios but not on those related to commerce. The limitation detected in our search through the literature is that data have been collected via non-experimental approaches only, with the mere description or graphical illustration of a chatbot interaction, but not the replication of a real-life scenario on an e-commerce platform [ 17 ]. For testing our hypotheses, two identical food e-commerce platforms were developed with Wix Website Builder.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Study 8 examined a potential solution: anthropomorphizing the algorithm. Extant work suggests that humanizing a nonhuman agent (e.g., referring to an object with a personal name) leads people to attribute human-like abilities to it (Crolic et al 2022; Epley 2018). We proposed that humanizing an algorithm should more closely align consumers’ perceptions of a human decision maker and an algorithmic decision maker, enabling the human-like algorithm to lead to more positive reactions than the non-human-like algorithm.…”
Section: What Can Managers Do To Mitigate the Negative Effects Of Alg...mentioning
confidence: 99%